FENOLOGI PEMBUNGAAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN MENGGUNAKAN DUA VARIETAS BERBEDA DI KEBUN PRAKTIK INSTITUT TEKNOLOGI SAWIT INDONESIA - Sri Murti Tarigan (Institut Teknologi Sawit Indonesia, 2022)
Oil palm plants are monocotyledonous plants where there are male flowers and female flowers in one tree, the appearance of oil palm flowers is at the base of the midrib, the average time at different stages of flower development. The T-Test sex ratio test was not significantly different. The photos shown refer to the standards set by BBCH (Biologische Bundesantalt Bundessortenamt und Chemische Industrie) explaining the stages of flower and fruit development in oil palm plants. Vegetative development includes plant height, number of leaves, rachis length, petiole thickness, number of leaflets, leaflets. The research was conducted at the Indonesian Palm Oil Institute (ITSI) Medan practice garden. The time of the study starts from August 2021 to March 2022. This study aims to determine and study the stages of flowering of oil palm plants in two different varieties by observing each flowering stage that occurs in oil palm plants. The method used is descriptive with qualitative and quantitative models. The results showed that the use of different varieties gave different results on the generative and vegetative growth of oil palm plants. The photos shown refer to the BBCH (Biologische Bundensartalt Bundessortenamt und Chemische Industrie) standard of flower development stages. The results of the T-test showed that the value of sex ratio, rachis length, petiole thickness, petiole cross section (LxT), number of leaflets on one side, length and width of leaflets, leaf area gave the effect of accepting H0 (not significantly different) while the T-test -Test on plant height, number of leaf fronts and total leaf area gave the effect of rejecting H0 (significantly different).